Investigation Type of Reasoning of Biology Prospective Teachers on Controversial Issues of The Theory of Evolution - Firdaus, Laras; Masiah, Masiah; Ibrohim, Ibrohim; Lestari, Sri Rahayu (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2021)
This study is a descriptive study that aims to explain the type of reasoning of biology prospective teachers on controversial issues of the theory of evolution. As much 26 prospective biology teachers at the Mandalika University of Education as participants. All participants are students who regularly program evolution courses in even semesters (2020/2021). A total of 3 open-ended question based on socioscientific issues (SSI) were used to obtain information about the type of reasoning of biology prospective teachers. The data analysis process was carried out descriptively, and based on the results of the study, that the type of reasoning of prospective biology teacher students was dominated by the type of reasoning based on religious beliefs and intuitive reasoning. These results indicate that the student biology prospective teachers not only conflict between religious beliefs and the theory of evolution, but also do not understand the concepts on the theory of evolution. Referring to the results of this study, further research is recommended to examine the acceptance or understanding, and beliefs of teachers, both in middle and high schools on the theory of evolution.